2006
DOI: 10.1021/jm051142c
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Sensitivity of the Human UDP-glucuronosyltransferases 2B7 and 2B17

Abstract: A set of 28 enantiomers comprising rigid and flexible secondary alcohols was synthesized by the asymmetric Corey-Bakshi-Shibata reduction. The enantiomerically pure alcohols were subjected to enzymatic glucuronidation assays employing the human UDP-glucuronosyltransferases (UGTs) 2B7 and 2B17. Both UGTs displayed high levels of stereoselectivity, favoring the conjugation of the (R)-enantiomers over their respective (S)-stereoisomers at eudismic ratios up to 256. The spatial arrangement of the hydroxy group det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that some UGT enzymes stereoselectively catalyze glucuronidation (Court et al, 2002;Tougou et al, 2004;Bichlmaier et al, 2006;Sten et al, 2006). In the present study, we characterized different human UGT enzymes for glucuronide formation using racemic 4Ј-HPPH.…”
Section: Discussionmentioning
confidence: 80%
“…It has been demonstrated that some UGT enzymes stereoselectively catalyze glucuronidation (Court et al, 2002;Tougou et al, 2004;Bichlmaier et al, 2006;Sten et al, 2006). In the present study, we characterized different human UGT enzymes for glucuronide formation using racemic 4Ј-HPPH.…”
Section: Discussionmentioning
confidence: 80%
“…UGT subtypes including UGT1A9, UGT1A10, UGT2B7, UGT2B15, and UGT2B17 can stereo-selectively catalyze the glucuronidation of substrates and affect their metabolites` pharmacological effects [26,[29][30][31][32][33] . However, there was no report on whether morphine antinociception can be enhanced via the selective alteration of its metabolite ratios by UGT2B7 allelic variants or dimerized with other UGTs.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (CDCl 3 ) δ: 7.43−7.39 (m, 1H), 7.30−7.21 (m, 3H), 5.22 (t, J = 6.0 Hz, 1H), 3.05 (ddd, J = 16.0, 8.5, 5.0 Hz, 1H), 2.81 (dt, J = 16.0, 7.5 Hz, 1H), 2.52−2.42 (m, 1H), 2.19 (br s, 1H), 1.99−1.88 (m, 1H). (R)-4-Methyl-2,3-dihydro-1H-inden-1-ol ((R)-8a) 26 (Scheme 2, 97% ee). [α] D 24 = −11.4 (c 1.46, CHCl 3 ); lit.…”
mentioning
confidence: 99%
“…[α] D 24 = −11.4 (c 1.46, CHCl 3 ); lit. 26 [α] D 23 = −36.3 (c 1.5, CHCl 3 ), 99% ee for R. HPLC (CHIRALPAK OD-3, i-PrOH/ hexane = 1/30, flow rate = 0.65 mL/min): t R = 23.9 min (1.7%), t R = 30.0 min (98.3%). 1 H NMR (CDCl 3 ) δ: 7.26 (d, J = 7.0 Hz, 1H), 7.18 (dt, J = 7.5, 7.0 Hz, 1H), 7.10 (d, J = 7.0 Hz, 1H), 5.24 (dd, J = 6.0, 5.5 Hz, 1H), 2.98 (ddd, J = 16.0, 8.5, 5.0 Hz, 1H), 2.73 (ddd, J = 16.0, 8.0, 7.0 Hz, 1H), 2.54−2.44 (m, 1H), 2.29 (s, 3H), 2.07 (br s, 1H), 1.99−1.90 (m, 1H).…”
mentioning
confidence: 99%
See 1 more Smart Citation